Penerapan Permainan Tradisional untuk Meningkatkan Minat Siswa pada Pembelajaran PJOK Kelas IV SDI. Al Mutmainnah Bringin Dasuk Sumenep - Moh. Yanto; Mas’odi; Noer Wachid Riqzal Firdaus (MAN Insan Cendekia Jambi, 2026)
This study was conducted with the aim of examining the extent to which the implementation of traditional games can foster students' interest in learning Physical Education, Sports, and Health (PJOK) at SDI Al Mutmainnah Bringin Dasuk Sumenep. The approach chosen was a quasi-experimental design.One Group Pretest-Posttest, namely a research model that compares the condition of a sample group before and after receiving intervention, through initial measurements (pretest) and final measurements (posttest). For analysis purposes, the data were processed using a paired mean difference test (paired sample t-test) to see whether there is a significant difference between the scores before and after the treatment is given. The statistical calculation results show a calculated t value of 4.29. This figure is then compared with the t table value at a 95% confidence level (α = 0.05) with 14 degrees of freedom (obtained from N – 1 = 15 – 1 = 14). Based on the two-way hypothesis test, the obtained t table value is 2.064. Because the calculated t (4.29) exceeds the t table (2.064), the alternative hypothesis (Hₐ) is accepted and the null hypothesis (H₀) is rejected. Thus, it can be concluded that there is a significant influence.